PERKEMBANGAN KOGNITIF PADA MASA ANAK-ANAK AWAL - Siregar, Nur Azizah (AL-QALAM: JURNAL KEPENDIDIKAN, 2023)
The purpose of this study is to describe how cognitive development in early childhood. This research identifies how and what cognitive developments occur in early childhood. This study uses the library research method in collecting data or information needed in the preparation of this article. The data or information comes from ebooks, books, articles and hail findings related to cognitive development in early childhood. According to Jean Piaget, early childhood is in the pre-operational stage, namely from the age of 2-7 years. At this stage children begin to use language and understand things symbolically. Children also begin to have the development of imagination and memory, at this stage children cannot understand the logic of adults, this is because children in the preoperational stage think according to their intuition not based on reality. Some cognitive developments that occur during this period are such as the development of theory of mind, language skills, execution functions, memory development and intelligence.